Analisis Dampak Perkembangan Pariwisata Terhadap Ekonomi Masyarakat: Studi Kasus Saliper Ate, Labuhan Badas, Kabupaten Sumbawa - Fikram Fikram; Edi Irawan (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
The development of tourism will have an impact on economic change in an area or region. The impacts caused by tourism development are positive impacts and negative impacts. Sumbawa Regency is aggressively developing tourism to utilise its high potential. This research uses a qualitative approach intending to understand the phenomenon of what is experienced by the research subject, and by way of description in the form of words and language, in a special context that is scientific and by utilising various natural methods. As descriptive research, this research contains descriptions, pictures or paintings systematically factual, accurate about the facts and relationships between the phenomena investigated. Data was collected through observation, interviews, and documentation at the Sumbawa Regency Youth, Sports and Tourism Office. Triangulation techniques were used to check the validity of the data. Management planning of Saliper Ate tourist attraction is very important to direct the development of tourism potential in a positive and sustainable manner. Cooperation from various relevant stakeholders is needed to encourage the development of Saliper Ate tourism in a synergistic and integrated manner. Tourism development in Saliper Ate increases tourist visits and pays attention to their needs.